The Effectiveness of Giving Growth Hormone to Children with Chronic Kidney Disease: Systematic Literature Review - Irhamni Nur Afdhila; Fitrisia Amelin; Gardenia Akhyar (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Chronic Kidney Disease (CKD) can cause growth problems in children. This condition will affect children’s social life and increase morbidity and mortality. Growth hormone (GH) is one of medication that has been used for treatment of impaired growth in children with chronic kidney disease. In Indonesia, this management has not been provided, because it is expensive and its effectiveness is uncertain. This research was conducted to determine the effectiveness of growth hormone in increasing linear growth in children with CKD. This study is a systematic review of the Randomized Controlled Trial (RCT) study to determine the effectiveness of growth hormone as a treatment for children with CKD. Literature search was conducted using five databases, namely Pubmed, Google Scholar, DOAJ, BMC and CENTRAL that matched the inclusion and exclusion criteria. The guide used in the literature selection was the PRISMA flow chart. A Total of 10 studies were included in the systematic review. Growth hormone is effective in increasing linear growth in children with CKD. Generally there was a significant increase in height (standard deviation (SD)), high velocity (SD or cm) in the therapy group compared to the control group. The dose of growth hormone that is given varies, but the most is 4 IU / m2 / day, once a day, by subcutaneous injection. The duration of growth hormone administration varied from 6 months to 5 years with an average of 1.7 years. Growth hormone did not aggravate kidney problems in children with CKD and can increase important factors in bone formation, namely alkaline phosphatase and osteocalcin.